Propuesta de la implementación del divorcio sin causa y de su convenio regulador en la legislación ecuatoriana - Urgilés Valle, Valeria Jacquelin (2015)
Family Law, pertaining to civil law governing relations and links that can arise from different types of families are born, exist and are modified according to the progress of society, all these links have to protect them. The Ecuador currently suffer from this vulnerability, lack of implementation of the rights specified in the Constitution and international treaties, but we have a standard full compliance with the law is still lacking. New legal concepts in family law seek to provide protection to new types of families, these no-fault divorce and the regulatory agreement, which figures on the right to privacy and autonomy of the parties is weighted as for his family and personal relationships. The no-fault divorce, seeking full compliance with the right to privacy that is in our Constitution and in international treaties to which Ecuador has ratified, this right is violated by maintaining a divorce cases in which they must prove guilt one of the spouses or failure of a marriage duty, also the will of the spouses is violated because it is necessary to have to resort to a cause in order to access the process. The Settlement Agreement is a document which seeks to prevail bargaining power of the parties to regulate the family situation after divorce proceedings, it is necessary to prime the autonomy of the spouses but is respected as it stipulated in the standard especially in the item on children and adolescents. The implementation of this legal concept has been socially relevant because it seeks to separate the marital relationship with the parental relationship and carried out better relationship after a divorce. Both figures have been renovated in legislation closer to our countries have supported its implementation in the previously mentioned rights and the need to comply with international human rights law, these modern reforms have to be given a constitutionalization of law which is the same family need in our country.